2008
DOI: 10.1111/j.1755-0998.2008.02159.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of microsatellite loci for Hymenaea courbaril and transferability to Hymenaea stigonocarpa, two tropical timber species

Abstract: Hymenaea courbaril is a tropical timber species, intensely exploited and found in the Amazon, Atlantic Forest and Brazilian Cerrado biome. Nine highly polymorphic microsatellite loci were developed from a genomic library enriched for AG/TC repeats. In a total of 41 individuals, from two natural populations, seven to 13 alleles per locus were detected and expected heterozygosity ranged from 0.75 to 0.90. Seven loci were effectively transferred to Hymenaea stigonocarpa. High levels of polymorphism make the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 5 publications
5
17
0
7
Order By: Relevance
“…Similar transferability rates for microsatellite markers with high levels of polymorphism have been reported in other studies of plants such as Arachis (Bravo et al, 2006) and Hymenaea (Ciampi et al, 2008) or those from different genera such as among the species of the Poaceae family (Elazreg et al, 2011). These results demonstrate that several species, which may or may not be closely related, can be analyzed without the need for designing specific primers.…”
Section: Transferability Of Ssr Markerssupporting
confidence: 60%
See 3 more Smart Citations
“…Similar transferability rates for microsatellite markers with high levels of polymorphism have been reported in other studies of plants such as Arachis (Bravo et al, 2006) and Hymenaea (Ciampi et al, 2008) or those from different genera such as among the species of the Poaceae family (Elazreg et al, 2011). These results demonstrate that several species, which may or may not be closely related, can be analyzed without the need for designing specific primers.…”
Section: Transferability Of Ssr Markerssupporting
confidence: 60%
“…Similar results for H E and H O were found in a population of P. lentiscus L. by using specific microsatellite markers (H E ranged from 0.291 to 0.848 and H O from 0.143 to 0.762) (Albaladejo et al, 2008). The mean values for H O and H E were also close to those found with heterologous SSR in H. stigonocarpa (0.389 and 0.601, respectively) (Ciampi et al, 2008) and in 2 populations of Tabebuia roseoalba (with average H O of 0.416 and 0.490 and H E of 0.773 and 0.740) (Feres et al, 2009 A = number of alleles per locus; H E = expected heterozygosity; H O = observed heterozygosity; f = coefficient of endogamy; Q = probability of paternity exclusion; I = probability of genetic identity; QC = combined probability of paternity exclusion; IC = combined probability of genetic identity. ns = non-significant values (P > 0.00455).…”
Section: Characterization Of the Polymorphic Ssr Locisupporting
confidence: 59%
See 2 more Smart Citations
“…Essa característica permitiu a realização de inúmeros estudos, dentre os quais pode-se destacar os trabalhos com espécies do Cerrado: Zucchi et al (2002) de Eucalyptus spp para Eugenia dysenterica; Martins et al (2006) de Capsicum spp para Solanum lycocarpum e Ciampi et al (2008) de Hymenaea courbaril para Hymenaea stigonocarpa, entre outros.…”
Section: Marcadores Microssatélitesunclassified